Study of efficacy of short course peri-operative antibiotics in clean contaminated surgeries - C. R., Shivakumar; Shoeb, Mohammad Fazelul Rahman; Pinate, Anil Reddy (International Surgery Journal, 2017)
Background: Surgical site infection is a one of the most common postoperative complication and causes significant postoperative morbidity and mortality. WHO described Hospital acquired infections as one of the major infectious diseases having huge economic impact. Perioperative antibiotics constitute the bulk of antimicrobial consumption in any hospital. We need to adapt the policies that decrease the incidence of postoperative wound infection. Methods: Patients undergoing elective surgeries for clean contaminated cases for various causes from 15th May 2014 to 15th June 2017 under Surgical 1st Unit of District hospital Gulbarga (Affiliated to Gulbarga Institute of Medical Sciences, Gulbarga) are included in our study. During this period, a total of 216 patients participated, of which 145 were males and 71 were females. Patients received two doses of perioperative antibiotics, first dose before surgery and second dose after surgery, 12 hours apart during this period. Results: In this study, surgical site infection rate is 2.3% in clean-contaminated surgeries. Conclusions: The findings indicate that a short course of perioperative antibiotics where in first dose is given 30 minutes to one hour before surgery and second dose is given 12 hours after surgery are sufficient and efficacious as infection rate is acceptable (1%-3%).Infection rate in our study was 2.3%. It is cost-effective as well for prevention of surgical site infections in clean-contaminated surgeries in Indian surgical setup.